Do motorways shape urban growth? Analysis of growth patterns with micro-level data – before and after road openings in two Danish motorway corridors - Thomas S. Nielsen; Henrik Harder Hovgesen (European Regional Science Association (ERSA), 2005)
The paper is an offspring from the Research project Town, Road and Landscape that aims to assess the effect of the Danish motorway network (specifically the last 20 years) on urban growth and interaction patterns. As one of the main interests of the project is the changing urban form and the changing character of the roadscape, the impact of the motorway is in part analysed with micro level data, spatial statistics and GIS – to allowing mapping of changing development trends in motorway corridors. The paper presents analysis of the impact of motorway openings on urban form in two Danish motorway corridors. The analysis is based on a before and after perspective – where the building activity and its location (building register with address coordinates) after the opening of the motorway is compared to building activity in the years before the construction of the motorway. Preliminary results suggest that the motorway most markedly influences the location of non-residential building activities within the city – in favour of locations near the entrance points to/from the motorway network. The development can be explained in part by municipal planning, which in some instances has opened up the new locations for development far ahead of market demand – and in part by an increasing demand for exposed and accessible sites for business development which still seems to be in its beginning.
Keywords: 330